Profane friendship - Brodkey, Harold (Farrar, Straus & Giroux, 1994)
A homosexual love affair between an American writer and an Italian actor in Venice. It begins when both are students, is interrupted by World War II, then resumes with full passion, only to turn into jealousy and hate.